HUMAN RESOURCE DEVELOPMENT IN THE APPARATUS AT THE REGIONAL REVENUE SERVICE OF PANGKEP DISTRICT - Ummu Safira Salsabila; Ani Susanti; Nuraisyah; Daswati; Syahruddin Hattab (RADJA PUBLIKA, 2026)
This study aims to analyze human resource development (HRD) among personnel at the Pangkep Regency Regional Revenue Agency (Bapenda) using the Human Resource Development (HRD) theory proposed by Holton and Swanson (2011), which emphasizes three main dimensions: learning, performance, and change. The research approach used was a qualitative case study method, and data were collected through in-depth interviews, observations, and documentation studies with the Head of the Agency, the Secretary, and several employees as key informants. The results show that in the learning dimension, training and development of personnel have been carried out, but are still general and not based on a clear needs analysis. In the performance dimension, training has an impact on increasing work effectiveness and productivity, but has not been balanced with a sustainable performance-based reward and evaluation system. Meanwhile, in the change dimension, there have been positive behavioral changes in the form of increased discipline, adaptability to information technology, and strengthening work ethics and professionalism. These findings indicate that HRD development at the Pangkep Regional Revenue Agency (Bapenda) has had a positive impact on personnel competence and behavior, although it still requires strengthening policies and institutions so that the three HRD dimensions can be fully integrated. This research confirms that HRD theory is relevant to be applied in the context of public bureaucracy because it is able to explain the relationship between learning, performance, and changes in organizational culture as the basis for creating competent and adaptive apparatus to the demands of modern public services.